AVALANCHE PHOTODIODE RECEIVER (2013)
A method of operating an avalanche photodiode includes providing an avalanche photodiode having a multiplication region capable of amplifying an electric current when subject to an electric field. The multiplication region, in operation, has a first ionization rate for electrons and a second, different, ionization rate for holes. The method also includes applying the electric field to the multiplication region, receiving a current output from the multiplication region, and varying the electric field in time, whereby a portion of the current output is suppressed.